Prevalence of dyslipidemia in middle-aged adults with NOS3 gene polymorphism and low cardiorespiratory fitness - Malagrino, Pamella A; Sponton, Carlos H G; Esposti, Rodrigo D; Franco-Penteado, Carla F; Fernandes, Romulo A; Bezerra, Marcos André C; Albuquerque, Dulcinéia M; Rodovalho, Cynara M; Bacci, Maurício; Zanesco, Angelina (Arquivos brasileiros de endocrinologia e metabologia, 2013)
To evaluate the influence of the interaction between endothelial nitric oxide synthase gene (NOS3) polymorphisms at positions -786T>C, Glu298Asp and intron 4b/a, and cardiorespiratory fitness on plasma nitrite/nitrate levels, blood pressure, lipid profile, and prevalence of cardiometabolic disorders. Ninety-two volunteers were genotyped for NOS3 polymorphisms at positions (-786T>C and Glu298Asp) and (intron 4b/a) and divided according to the genotype: non-polymorphic (NP) and polymorphic (P). After that, they were subdivided according to the cardiorespiratory fitness associated with genotype: high (HNP and HP) and low (LNP and LP). The subjects with polymorphism for the interactions at positions Glu298Asp + intron 4b/a, and Glu298Asp+-786T>C showed the highest values in total cholesterol, as well as dyslipidemia. Our findings show that NOS3 gene polymorphisms at positions -786T>C, Glu298Asp, and intron 4b/a exert negative effects on the lipid profile compared with those who do not carry polymorphisms.